Association of inflammation-related and microRNA gene expression with cancer specific mortality of colon adenocarcinoma - Schetter, Aaron J. (2009)
TRANSLATIONAL RELEVANCE: We report that the expression pattern of inflammatory-related genes in tumors and paired noncancerous tissues was an independent prognostic marker for colon adenocarcinoma patients. This gene signature was associated with prognosis in early stage patients. Therefore, this gene signature may be useful to identify high risk, early stage patients to assist in decisions regarding appropriate therapeutic intervention. We also show that combining independent biomarkers can improve predictions over single biomarkers. The combination of the inflammatory gene signature with available microRNA-21 expression data improved predictions with prognosis over either alone. These findings demonstrate the potential of IRS and/or microRNA-21 to be used as prognostic biomarkers for early stage colon cancer. PURPOSE: Inflammatory genes and microRNAs have roles in colon carcinogenesis; therefore, they may provide useful biomarkers for colon cancer. This study examines the potential clinical utility of an inflammatory gene expression signature as a prognostic biomarker for colon cancer in addition to previously examined microRNA-21 expression. EXPERIMENTAL DESIGN: Quantitative RTPCR measured the expression 23 inflammatory genes in colon adenocarcinomas and adjacent noncancerous tissues from 196 patients. These data were used to develop models for cancer-specific mortality on a training cohort (n=57) and this model was tested in both a test (n=56) and validation (n=83) cohort. Expression data for microRNA-21 was available for these patients and was compared to and combined with inflammatory gene expression. RESULTS: PRG1, IL-10, CD68, IL-23a, and IL-12a expression in noncancerous tissue and PRG1, ANXA1, IL-23a, IL-17a, FOXP3 and HLA-DRA expression in tumor tissues were associated with poor prognosis based on Cox regression (|Z-score| > 1.5) and were used to generate the inflammatory risk score (IRS). IRS was associated with cancer-specific mortality in the training, test (P=0.01) and validation (P=0.02) cohorts. This association was strong for stage II cases (P=0.002). microRNA-21 expression was associated with IL-6, IL-8, IL-10, IL-12a and NOS2a, providing evidence that the function of this microRNA and these inflammatory genes are linked. Both IRS and microRNA-21 expression were independently associated with cancer-specific mortality, including stage II patients alone. CONCLUSION: IRS and microRNA-21 expression are independent predictors of colon cancer prognosis and may provide a clinically useful tool to identify high risk patients.